Advanced endoscopic resection for colorectal dysplasia in inflammatory bowel disease: a meta-analysis - Mohapatra, Sonmoon; Sankaramangalam, Kesavan; Lopimpisuth, Chawin; Moninuola, Oluwatoba; Simons, Malorie; Nanavati, Julie; Jager, Leah; Goldstein, Debra; Broder, Arkady; Akshintala, Venkata; Chowdhury, Reezwana; Parian, Alyssa; Lazarev, Mark G.; Ngamruengphong, Saowanee (Endoscopy International Open, 2022)
Background and study aims Little is known about outcomes of advanced endoscopic resection (ER) for patients with inflammatory bowel disease (IBD) with dysplasia. The aim of our meta-analysis was to estimate the safety and efficacy of endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) for dysplastic lesions in patients with IBD.Methods We performed a systematic review through Jan 2021 to identify studies of IBD with dysplasia that was treated by EMR or ESD. We estimated the pooled rates of complete ER, adverse events, post-ER surgery, and recurrence. Proportions were pooled by random effect models.Results Eleven studies including 506 patients and 610 lesions were included. Mean lesion size was 23 mm. The pooled rate of complete ER was 97.9 % (95 % confidence interval [CI]: 95.3 % to 99.7 %). The pooled rate of endoscopic perforation was 0.8 % (95 % CI:0.1 % to 2.2 %) while bleeding occurred in 1.6 % of patients (95 %CI:0.4 % to 3.3 %). Overall, 6.6 % of patients (95 %CI:3.6 % to 10.2 %) underwent surgery after an ER. Among 471 patients who underwent surveillance, local recurrence occurred in 4.9 % patients (95 % CI:1.0 % to 10.7 %) and metachronous lesions occurred in 7.4 % patients (95 %CI:1.5 % to 16 %) over a median follow-up of 33 months. Metachronous colorectal cancer (CRC) was detected in 0.2 % of patients (95 %CI:0 % to 2.2 %) during the surveillance period.Conclusions Advanced ER is safe and effective in the management of large dysplastic lesions in IBD and warrants consideration as first-line therapy. Although the risk of developing CRC after ER is low, meticulous endoscopic surveillance is crucial to monitor for local or metachronous recurrence of dysplasia.